Gentlemen Emigrants: From the British Public Schools to the Canadian Frontier - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1983)
This article reviews the book, "Gentlemen Emigrants: From the British Public Schools to the Canadian Frontier," by Patrick A. Dunae.